Raíces griegas de la construcción de la feminidad en los refranes españoles - Pascual López, Xavier (Romanica Silesiana)
Ancient Greek Origins of the Construction of Femininity in Spanish Proverbs This paper intends to trace, in Ancient Greek philosophy and oral literature (particularly in Hesiod, Homer and Aristotle), possible roots of the image of women transmitted through Spanish proverbs. In this paper, proverbs are conceived as cultural products which reflect the worldview of the community that once coined them and, at the same time, they are understood as a power tool which guides the interpretation of reality and influences human behavior. The article states that the image of femininity was built from the masculine perspective, which defined it through a process of estrangement emerged from considering women as “the other” and from projecting on that image men’s point of view on how women are and how they should be. Key words: femininity, verbal art, folk literature, Spanish proverbs, Ancient Greek literature and philosophy.